(untitled) (Global Journal of Human-Social Science, 2014)
Today, excess density of population in city and it is increasing growth in bulk is led to demand and attention to urban development. Demand for urban development is one of the most important issues against human in future. Therefore, to solve this problem and obstacles, safety system of city should be developed along this to cover whole city. The most important problem about the services of fire stations is the inappropriate distribution of stations and restricted function area of present stations. So, qualities and quantities distribution of stations is investigated scientifically and professionally. Using traditional methods planning fire stations for services mean wasting papers and time, but today, using GIS serves as a tool to create proper and effective database.